2006
DOI: 10.1007/s10530-006-9033-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the establishment of a non-native annual grass influences competitive interactions with Mojave Desert perennials

Abstract: Competition between native and nonnative species can change the composition and structure of plant communities, but in deserts, the highly variable timing of resource availability also influences non-native plant establishment, thus modulating their impacts on native species. In a field experiment, we varied densities of the nonnative annual grass Bromus madritensis ssp. rubens around individuals of three native Mojave Desert perennials-Larrea tridentata, Achnatherum hymenoides, and Pleuraphis rigida-in either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…The late season precipitation patterns can afford advantages to different functional groups depending on the timing and the amount of resources available during the pulse versus inter-pulse periods (James and Richards 2006;James et al 2009). Invasive Mojave Desert annuals have the potential to use water and N more rapidly than native annual species (DeFalco et al 2003); however, invasive annuals established in response to later season rainfall have less competitive potential (James and Richards 2006;DeFalco et al 2007). While moisture availability may be more influential during other years, our data show that N availability was correlated with native and invasive annual plant production under seasonal drought.…”
Section: Post-fire Inorganic N Influences Annual Plant Composition Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The late season precipitation patterns can afford advantages to different functional groups depending on the timing and the amount of resources available during the pulse versus inter-pulse periods (James and Richards 2006;James et al 2009). Invasive Mojave Desert annuals have the potential to use water and N more rapidly than native annual species (DeFalco et al 2003); however, invasive annuals established in response to later season rainfall have less competitive potential (James and Richards 2006;DeFalco et al 2007). While moisture availability may be more influential during other years, our data show that N availability was correlated with native and invasive annual plant production under seasonal drought.…”
Section: Post-fire Inorganic N Influences Annual Plant Composition Anmentioning
confidence: 99%
“…Precipitation pulses influence N availability to plants, and the timing of these pulses can affect the survival and competitive ability of desert plants (James and Richards 2006;DeFalco et al 2007;Rao and Allen 2009). The timing of resource pulses and the consequent response by plants may be altered by wildfire but has not been documented for desert systems.…”
mentioning
confidence: 99%
“…The remaining question is whether the observed differences in native plant assemblages were caused by or merely correlated with the presence of L. salicaria or P. australis. L. salicaria and P. australis may have influenced the plant species composition and abundance by impacting nutrient cycling (Chambers et al 1999;Findlay and Groffman 1997), physical structure of the landscape, light access (Odum et al 1984;Gaudet and Keddy 1988;Edwards et al 1995;Minchinton and Bertness 2003), possibly flooding regimes, and availability of space (Hager and McCoy 1998). However, research conducted by Lenssen et al (1999) suggested that native species richness and plant assemblages in areas of low elevation may be merely correlated with the presence of L. salicaria or P. australis and caused by abiotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…(common reed) invade freshwater wetlands. Both are considered to have negative effects on the native plant community they invade by ''overgrowing'' the native wetland flora and forming a monoculture (Odum et al 1984;Rawinski and Malecki 1984;Gaudet and Keddy 1988;Edwards et al 1995;Minchinton and Bertness 2003). Hager and McCoy (1998) noted the lack of data in support of the hypothesis that L. salicaria reduces plant diversity and species richness.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, alien grasses increase and dominate communities while native perennial species decline due to fires (O' Leary and Minnich, 1981;McLaughlin and Bowers, 1982;Brown and Minnich, 1986;Esque et al, 2004;Brooks and Berry, 2006). Furthermore, the invasive Mediterranean annual grasses can outcompete native species for limited resources (Salo, 2004;DeFalco et al, 2007) and can outnumber native annuals after fires (Brooks, 1999a).…”
Section: Introductionmentioning
confidence: 99%